2011
DOI: 10.1139/f10-132
|View full text |Cite
|
Sign up to set email alerts
|

Intracohort and intercohort spatial density dependence in juvenile brown trout (Salmo trutta)

Abstract: An increased mobility with age can be expected for many organisms, which will reduce the potential for spatial density dependence. Here we quantify the extent of spatial density dependence for two juvenile age classes of brown trout ( Salmo trutta ) that differ in their dispersal abilities. As predicted, spatial variation in intracohort density had a strong effect on the performance of underyearlings, but not on yearlings. However, rather surprisingly, local underyearling density influenced the energetics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
13
2
Order By: Relevance
“…Despite the fact that younger individuals cannot out-compete older ones, increasing density of younger trout results in increased metabolic costs associated with guarding and defending territories and thus reduces the growth of older trout. Similar results were found by Kvingedal and Einum (2011) in Atlantic salmon. In addition, higher densities of younger age-classes would depress growth of older ones through exploitative competition for food, since even if younger individuals cannot out-compete older ones they can consume prey that otherwise would have been available to older age-classes.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the fact that younger individuals cannot out-compete older ones, increasing density of younger trout results in increased metabolic costs associated with guarding and defending territories and thus reduces the growth of older trout. Similar results were found by Kvingedal and Einum (2011) in Atlantic salmon. In addition, higher densities of younger age-classes would depress growth of older ones through exploitative competition for food, since even if younger individuals cannot out-compete older ones they can consume prey that otherwise would have been available to older age-classes.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the predation by avian predators, such as herons Ardea cinerea and kingfisher Alcedo atthis (which have both been observed along the river), may be increased during low-flow periods. Conversely, we did not detect any effect of the 0+ density on the growth of age 1+ as reported by Kvingedal & Einum (2011). Einum et al (2006) demonstrated that the 0+ density did not affect summer survival but strongly affected dispersal.…”
Section: Discussioncontrasting
confidence: 45%
“…In two recent studies on brown trout in Sweden, Kaspersson and Hö jesjö (2009) found that the presence of yearling fish was associated with an overall reduction in subyearling growth rates, and Kaspersson et al (2013) reported on reduced growth rates, rather than increased mortality rates and movement, in small individuals when experimentally adding large brown trout to stream sections. Oppositely, Kvingedal and Einum (2011) found that subyearling brown trout densities in Norway were associated with depressed size-at-age for both subyearling and yearling fish, and that yearling density did not cause depressed sizes in either age class. Parra et al (2012) reported on density-dependent effects both within and among cohorts of brown trout in northern Spain, and notably that the size of overyearling fish was negatively associated with densities of younger cohorts.…”
Section: Discussionmentioning
confidence: 92%